Do all roads lead to Rome? Exploring community trajectories in response to anthropogenic salinization and dilution of rivers. (21st January 2019) - Gutiérrez-Cánovas, Cayetano; Sánchez-Fernández, David; Cañedo-Argüelles, Miguel; Millán, Andrés; Velasco, Josefa; Acosta, Raúl; Fortuño, Pau; Otero, Neus; Soler, Albert; Bonada, Núria
Abstract : Abiotic stress shapes how communities assemble and support ecological functions. However, it remains unclear whether artificially increasing or decreasing stress levels would lead to communities assembling predictably along a single axis of variation or along multiple context-dependent trajectories of change. In response to stress intensity alterations, we hypothesize that a single trajectory of change occurs when trait-based assembly prevails, while multiple trajectories of change arise when dispersal-related processes modify colonization and trait-filtering dynamics. Here, we tested these hypotheses using aquatic macroinvertebrates from rivers exposed to gradients of natural salinity and artificially diluted or salinized ion contents. Our results showed that trait-filtering was important in driving community assembly in natural and diluted rivers, while dispersal-related processes seemed to play a relevant role in response to salinization. Salinized rivers showed novel communities with different trait composition, while natural and diluted communities exhibited similar taxonomic and trait compositional patterns along the conductivity gradient. Our findings suggest that the artificial modification of chemical stressors can result in different biological communities, depending on the direction of the change (salinization or dilution), with trait-filtering, and organism dispersal and colonization dynamics having differential roles in community assembly. The approach presented here provides both empirical and conceptual insights that can help in anticipating the ecological effects of global change, especially for those stressors with both natural and anthropogenic origins. This article is part of the theme issue 'Salt in freshwaters: causes, ecological consequences and future prospects'.